2010
DOI: 10.1523/jneurosci.2985-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Promotes Microglia to Uptake and Degrade Amyloid β Peptide through Upregulation of Mouse Formyl Peptide Receptor 2 and Induction of Insulin-Degrading Enzyme

Abstract: Locus ceruleus (LC) is the main subcortical site of norepinephrine synthesis. In Alzheimer's disease (AD) patients and rodent models, degeneration of LC neurons and reduced levels of norepinephrine in LC projection areas are significantly correlated with the increase in amyloid plaques, neurofibrillary tangles, and severity of dementia. Activated microglia play a pivotal role in the progression of AD by either clearing amyloid ␤ peptide (A␤) deposits through uptake of A␤ or releasing cytotoxic substances and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 75 publications
6
77
1
Order By: Relevance
“…Microglia are also well known phagocytes and sources of cytokines and other proinflammatory mediators (22, 60 -63). Both ATP and NE have been reported to separately modulate these functions (11,19,20,46,64). Interestingly, NE pretreatment prevents the ATP-induced p38 phosphorylation and tumor necrosis factor-␣ (TNF-␣) release by mouse spinal cord microglia (41), suggesting that adrenergic signaling and purinergic signaling might interact at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia are also well known phagocytes and sources of cytokines and other proinflammatory mediators (22, 60 -63). Both ATP and NE have been reported to separately modulate these functions (11,19,20,46,64). Interestingly, NE pretreatment prevents the ATP-induced p38 phosphorylation and tumor necrosis factor-␣ (TNF-␣) release by mouse spinal cord microglia (41), suggesting that adrenergic signaling and purinergic signaling might interact at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“…First, NE might enhance microglial chemoattraction to the amyloid ␤ peptide (A␤)-containing plaques associated with the disease (19). Second, it promotes the clearance of A␤ plaques by increasing microglial phagocytosis of A␤ and elevating the expression of A␤-degrading enzymes (20). Third, NE treatment prevents the A␤-induced increase in proinflammatory cytokine expression (11,19), and lack of NE exacerbates microgliosis in a mouse model of Alzheimer disease (21).…”
mentioning
confidence: 99%
“…Furthermore, IDE expression and activity can be regulated by several signaling pathways that have been previously connected with AD development, e.g. estradiol [232], norepinephrin [233], NOTCH [234], ApoE [235], PPARγ [236] or S-nitrosylation [237]. Meta-analysis performed by Zhang et al suggested the association between IDE polymorphism and AD [238].…”
Section: Insulin-degrading Enzyme (Ide)mentioning
confidence: 99%
“…Accordingly, we suggest that a major effect of P2Y 2 R upregulation in the CNS is to delay the progression of neurodegeneration that occurs with chronic inflammation. It is known that activated astrocytes and microglia internalize and degrade Aβ [217][218][219][220][221], a mechanism that reduces Aβ toxicity in neurons, which is postulated to cause neuronal death in AD. Recruitment of activated microglia to sites of inflammation enhances the phagocytosis of aggregated Aβ via the F c receptor [222,223].…”
Section: P2y 2 Rs In Cns Inflammationmentioning
confidence: 99%